Models of income determination - National Bureau of Economic Research (Princeton : Princeton University Press, 1964)
This book is about income determination which reflect an attempt to bring together economies and statistician interested in national income theory and measurment
"Studies in income and wealth, volume 28 by the conference on research in income and wealth".
"A report of the National Bureau of Economic Research."
Includes bibliographical references and index.
oo 25/09/2018
Loans
Keywords: Income